Griscelli syndrome type 2 with deletion of entire RAB27A gene - Ravi Shankar,; Nita Radhakrishnan,; Savitri Singh, (Indian Journal of Case Reports, 2020)
Griscelli syndrome (GS) type 2 is a rare autosomal recessive disorder caused by mutation of RAS-associated protein RAB27A gene located on chromosome 15. It is a hyper-inflammatory disorder with partial albinism and immunological impairment and/or severe neurological impairment. We describe the case of a 2.5-month-old boy with classic features of GS type 2 with early-onset hemophagocytic lymphocytic histiocytosis (HLH) and multiple recurrences. Genetic testing found homozygous loss of 68 kbp of RAB27A gene at chromosome 15 at cytoregion q21.3, suggestive of deletion of exons 1–5. This genotype of large deletion correlated with the clinical severity. He was managed as per HLH 2004 protocol and was awaiting bone marrow transplantation when he succumbed to his illness. The case is being presented not only as the disease is rare but also the mutation identified is extremely rare and awareness of it will help clinicians to manage the case appropriately.